The effect of safety culture on the safety behavior of ship deck officers- empirical evidence from shipping industry - Xi, Yongtao; Wang, Zhijie; Hu, Shenping; Han, Bing; Yin, Jingbo (Frontiers in Marine Science, 2025)
IntroductionThe creation of safety culture in shipping industry is an important measure for reducing ship accidents and improving navigation safety. On the basis of literature review and theoretical assessments, this paper puts forward the conceptual logical framework and research hypotheses of safety culture and safety behavior. The purpose of this paper is to explore the effect of safety culture on ship officers' safety behavior.MethodThis paper developed a scale by referring to the well-established safety culture and safety behavior scales proposed in previous literature and combined with the shipping background. Based on self-reported questionnaire and primary data collected from 229 deck officers and captains from a shipping company in Shanghai, a relationship model between safety culture and safety behavior was constructed using structural equation modeling (SEM), and empirical tests were conducted to explore the impact of safety culture on ship officers’ safety behavior.ResultsThe results show that safety culture has a positive impact on ship officers’ safety behavior, in which safety material culture has a positive impact on safety compliance behavior, safety system culture has positive impacts on safety compliance behavior and prosocial safety behavior, while safety management culture and safety value fit have positive impacts on all dimensions of ship officers’ safety behavior.DiscussionThis paper proposes and validates a new model that can help explore the impact of safety culture on the safety behavior of ship officers. The research results indicate that we can improve ship officers’ safety behavior from two dimensions: safety management culture and safety value fit. More importantly, the research findings can help shipping companies develop measures to improve ship officers’ behavior based on their own circumstances, thereby reducing the likelihood of maritime accidents. The results of this paper will contribute to the development of safety management in shipping industry.